Scaling analysis of the thermal hydraulic behavior in the secondary side of steam generator. (15th December 2021) - Wang, L.S.; Yan, B.H.
Highlights: A scaling analysis for the thermal hydraulic phenomenon in the secondary side of steam generator is conducted. The scaling analysis is decomposed into three processes, natural circulation, forced convection and lateral flow. The similarity of heat transfer could be achieved by adjusting the parameters of primary side. The conventional scaling method could not realize the similarity of transverse flow. Abstract: Steam generator is one of the key facilities in nuclear power plant. Due to its complex structure and huge volume, the experimental and numerical research of steam generator needs a large amount of costs and computational resources. One feasible method is to replace the prototype steam generator with a model by the scaling analysis. In this work, a systematical scaling analysis for the thermal hydraulic phenomenon in the secondary side of steam generator in ocean motions is carried out. The scaling analysis is decomposed into three processes, natural circulation, forced convection and lateral flow. A series of scaling criteria are obtained. It is found that the similarity of heat transfer could be achieved by adjusting the parameters of the primary side. It is also revealed that the conventional scaling method could not guarantee the similarity of transverse flow due to the improper similarity of lateral resistance. Besides that, the scaling criteria for the amplitude and period are also obtained, which could be used in the subsequent experiments and numerical simulation.